A modernização da gestão da escola pública estadual do Rio Grande do Sul: a democracia na porta giratória - Drabach, Neila Pedrotti (2010)
The present dissertation aimed at discussing and issuing the challenges to democracy in the management of public education from the new benchmarks for public management revealed through changes in the world work and the role of the state, considering the object of study as the proposal "modernization of educational management" in force in state government of Rio Grande do Sul (Yeda Crusius Management 2007-2010). Thus, we find historically the issue between the project of construction of the democratic management as a constitutional principle and the new pattern of management (managing administration), now being incorporated into public administration from the movement of state reform, as driven strategy of overcoming the capitalist crisis of the 1970s. Given this paradoxical scenario analyzes the path of democratic management of public education the state of RS from the first movements to build this logic of management, it highlights the progress and constrains the issues, facing the adoption of management practices by state governments. Therefore, focusing on the propositions of the current government for education, it is analyzed by means of desk research, the proposed "modernization of educational management" with reference to the actions of the project Professor Nota 10 Valorização do Magistério (A Grade Teacher valorization of the Teaching), which is part of the Project Programa Estruturante Boa Escola para Todos (Structuring a Good School to Everybody) which includes guidelines for action of the State Department of Education and partnerships with private institutions to improve teaching quality through management strategies: Consultancy for the Quality of Education - SESI - RS and the Project Future Youth as a partnership with Unibanco. From the analysis of the documents, guided by the technique of content analysis, it became clear that the proposed "modernization of educational management" is woven into the management model that forms part of the government, which is driven by NGOs specializing in management consultancy, the proposals of Agenda 2020 and the requirements for the loan of the state at the World Bank, aiming at the inclusion of "modern management practices" in order to adjust to the State. The analysis of the proposed change in state law for Democratic Management, inserted in the Project Professor Nota 10 points to the introduction of management inspired by the business community, such as management contracts and meritocracy, in order to increase the efficiency and effectiveness of spending education, reshaping the autonomy and participation of the school community for the implementation of contracted targets. Regarding the projects of public-private partnerships, highlights the integration of business management model of capitalist values of competitiveness and awards in schools and private funding in education, reporting the logic of publicity departments of State and the inclusion of emergent markets in education. The introduction of these mechanisms in school management decharacterizes the project of democratic management, a time which reprocesses the educational management techniques and introduces the private management at the expense of the active participation of the school community, adopting the logic of capitalist management education, which had been strongly criticized in the 1980s.